Coronavirus And Diabetes-Future Directions: A Review (International Journal of Food and Nutritional Sciences, 2022)
Novel Coronavirus-2019 (nCoV-2019) was recognized in the Hubei province of Wuhan in China in December 2019. Epidemiological studies confirmed that age and people with pre-existing conditions, including diabetes (from mild to severe), CVD, hypertension, obesity, and chronic lung disease are at a very high risk of severe illness from coronavirus (COVID-19) are also associated with increased mortality. The reason behind this challenge is a low understanding of the molecular co-existence of the nCoV-2019 patient with diabetes and related comorbidities. At present, what we know about virus entry is the following, the viral spike (S) coat protein engages the human angiotensin-converting enzyme2 (ACE2) cell surface protein to invade the host cell. On the other hand, ACE2 expression/activity is reported to decrease with diabetic conditions (and related complications), and interestingly ACE2 expression gets upregulated during anti-diabetic therapies such as thiazolidinediones. The ACE2 upregulation provides rescuing effects in this metabolic illness; however, contrarily, ACE2 upregulation provides a suitable environment for this opportunistic virus to find more ACE2 and invade new cells. Interestingly ACE2 polymorphism and tissue-specific expression/activity of ACE2 are associated with various metabolic diseases and may act as an independent factor for a predisposing individual toward COVID-19 infection. We here depicted commonly shared signaling pathways between nCoV-2019 and mild to severe diabetes. Thus, overall the combination of ACE2 polymorphism, differential expression of ACE2, and the ability of some therapeutic agents to enhance ACE2 makes such individuals more prone to COVID-19 infection. We concluded this review with some exploratory novel approaches that can be utilized for targeting nCoV-2019 patients with certain mild to severe metabolic comorbidities.